INCIDENCE AND RISK FACTORS OF MULTISYSTEM INFLAMMATORY SYNDROME IN CHILDREN (MIS-C) AMONG PEDIATRIC PATIENTS RECEIVING CARE IN A TERTIARY HOSPITAL IN CENTRAL THAILAND - Narknok, Nutthaporn; Sakboonyarat, Boonsub (Journal of Southeast Asian Medical Research, 2023)
Background: Multisystem Inflammatory Syndrome in Children (MIS-C) involves severe complications after contracting SARS-CoV-2. Nevertheless, limited evidence is available of MIS-C incidence in Thailand. Therefore, the present study aimed to determine MIS-C incidence and its risk factors among Thai children. Methods: A retrospective cohort study was conducted between 2020 and 2021. The data were obtained from medical records of pediatric patients under 15 years receiving a diagnosis of SARS-CoV-2 and obtaining treatment at Ananda Mahidol Hospital, Lopburi Province, central Thailand. The World Health Organization defined MIS-C incidence as occurring within eight weeks after contracting SARS-CoV-2. A multivariable Cox proportional hazard regression model was used for estimating the adjusted hazard ratio (AHR) and 95% confidence interval (CI) for factors associated with MIS-C. Results: Three thousand pediatric patients with a history of SARS-CoV-2 were included in the present study. The majority (51%) were males. The median time of follow-up was 56 days. Twenty-five patients (0.83%) developed MIS-C, representing an incidence rate of 14.95 (95% CI: 9.67–22.07) per 100,000 person-days. The incidence rates among males and females were 18.77 (95% CI: 10.73–30.49) and 10.97 (95% CI: 5.02–20.83) per 100,000 person-days, respectively (p-value = 0.192). After adjusting for potential confounders, independent risk factors for MIS-C included a history of asthma (AHR: 7.65; 95% CI: 1.69–34.67), history of allergic rhinitis (AHR: 15.71; 95% CI: 5.73–43.05), history of nephrotic syndrome (AHR: 49.6; 95% CI: 5.89–417.06), every 10 mg/dL increase of C-reactive protein (AHR: 1.71; 95% CI: 1.28–2.29) and having COVID-19-related symptoms involving at least two systems (AHR: 9.36; 95% CI: 2.2–39.78) compared with those involving less than two systems. Conclusion: A modest incidence of MIS-C was estimated among Thai children, while a higher incidence of MIS-C among male patients was observed. Factors associated with MIS-C included underlying diseases and elevated C-reactive protein levels in SARS-CoV-2.